ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE WEBSITE PEJABAT PENGELOLA INFORMASI DOKUMENTASI (PPID) PADA SEKRETARIAT JENDERAL DPD RI MENGGUNAKAN METODE USER CENTERED DESIGN - Fikry Ardi Fatma (2022)
The Secretariat General of the DPD RI has a website called the Information Management and Documentation Officer (PPID) which has a function as a center for collecting, structuring, and storing public information from all work units within the Secretariat General of the DPD RI. However, the website still has drawbacks, namely there is no friendly user which results in users submitting requests and documents seeking information documentation, this is supported by data analysis that has been carried out that there is no information that explains the status of the application for user documentation, thus making documentation - Documentation or information is not channeled properly. Therefore, it is necessary to redesign the website as a solution to the problem. The method used is the User Centered Design (UCD) method which can create an interactive website system that focuses on the user. In the process of website analysis and development, questionnaires were distributed using the System Usability Scale (SUS) method with respondents using PPID DPD RI. The evaluation that will be carried out is to analyze the current system and provide repair solutions that will be tested using respondents. Thus, this study can provide future recommendations for PPID DPD RI. the assessment of the results of the evaluation carried out there has been an increase in good scores and fulfills the usefulness that is on the appearance of the PPID website of the Secretariat General of DPD RI.